Analysis of Motherhood in African American Literature: Exploring Sociocultural and Gender Representations - Amanova Madina Xamid qizi (Scientific Trends, 2023)
The article reveals sociocultural and gender perspectives, with a focus on black feminist theories, to dive into the complexities of black motherhood in African American literature. Each theory offers unique insights into the portrayal of black women and mothers in literary works, while also applying black feminist principles to highlight the specific experiences of black mothers.
Keywords: Feminists, Black Mothers, Domesticated Motherhood, Liberal Motherhood, Racism.